Problems and prospects for U.S. agriculture in world markets - Josling, Timothy; NPA Committee on Changing International Realities (Washington, D.C. : NPA Committee on Changing International Realities, 1981)
This study was essentially completed in 1979, before the U.S. embargo on the sale of 17 million tons of grain to the Soviet Union in January 1980
Includes bibliographical references.
osc 20/08/2019
Keywords: Produce trade; Export marketing; United States